The impact of metabolic dysfunction-associated steatotic liver disease on the efficacy of pegylated interferon-based therapy in patients with chronic hepatitis B - Han, Jiaxin; Xu, Lianxin; Li, Yuqin; Wang, Ziling; Zeng, Minghui; Gao, Jieru; Mi, Yuqiang; Kuai, Wentao; Xiang, Huiling; Xu, Liang (Frontiers in Immunology, 2026)
IntroductionThe impact of metabolic dysfunction-associated steatotic liver disease (MASLD) on the efficacy and prognosis of pegylated interferon (Peg-IFN)-based therapy for chronic hepatitis B (CHB) remains controversial and requires further investigation.MethodsA total of 620 CHB patients receiving Peg-IFN-based therapy were enrolled and categorized into MASLD-CHB (n = 247) and CHB (n = 373) groups. Propensity score matching (PSM) was employed to balance baseline differences. Kaplan-Meier survival analysis and LASSO-Cox regression were applied to identify independent predictors of complete virological response (CVR) and hepatitis B surface antigen (HBsAg) seroclearance.ResultsAfter PSM, 247 patients were included in each group. Compared with the MASLD-CHB group, the CHB group exhibited significantly higher cumulative CVR rates at month 3 (36.84% vs. 24.54%, p = 0.041), month 12 (77.19% vs. 62.72%, p = 0.013), end of treatment (EOT) (78.94% vs. 65.45%, p = 0.019), and end of follow-up (EOF) (80.70% vs. 68.18%, p = 0.026). The median time to the first CVR was shorter in the CHB group (4.4 vs. 5.5 months, p = 0.030). LASSO-Cox regression revealed HBV DNA (HR: 0.486, 95% CI: 0.297-0.793, p = 0.004), MASLD (HR: 0.736, 95% CI: 0.550-0.986, p = 0.040), HBsAg (HR: 0.808, 95% CI: 0.706-0.926, p = 0.002), HBeAg positivity (HR: 0.611, 95% CI: 0.433-0.862, p = 0.005), and triglycerides (HR: 0.793, 95% CI: 0.661-0.951, p = 0.012) as independent suppressors of CVR. Multiple factors were associated with HBsAg seroclearance (p < 0.05). At the EOF, the MASLD-CHB group had higher liver stiffness measurement values (8.10 [6.40, 9.60] vs. 6.20 [5.00, 7.50]) and a greater proportion of moderate-to-severe fibrosis (18.7% vs. 5.9%, p < 0.01).ConclusionIn CHB patients receiving Peg-IFN-based therapy, concurrent MASLD may impede the reduction of HBV DNA levels, delay the time of first CVR, and potentially accelerate liver fibrosis progression.